Interface design of a decision-support system for understanding the environmental impact of an organization - A study exploring nudging techniques and interaction design strategies in the context of supporting decision-making within an organization - KERNEHED, FELICIA (My University, 2020)
To keep global warming under 1,5 degrees Celsius is a core goal for the environmental and sustainability work in Sweden and many other UN countries today. Many organizations, that run big operations and have a high impact on the greenhouse gas emissions being released into the atmosphere, want to take their responsibility and reduce their carbon footprint. For an organization to enhance its prospects towards this goal, they need to understand the environmental impact of their operational activities, including gathering knowledge regarding potential improvements. This master’s thesis contributes to the above need by presenting suggested use of interaction design strategies and nudging techniques within the context of interface design of a decision-support system in the form of a desktop tool built around an organization’s emission data. A prototype visualizing the above contribution presents a design proposal of such a system. Higher educational institutions are the representative organization type targeted during this project which is grounded in desires and visions of the company Svalna who initialized the thesis work. Furthermore, The report presents the design process, including user research, workshops, definition and validation of tool requirements, ideation, and evaluation of the prototype through reviews with UX experts.
Keywords: Sustainability; carbon footprint; decision support system; nudging; interaction design